Use of Maximum Surgical Order Schedule (MSBOS) among pediatric patients to optimize blood utilization - Johann Paulo S. Guzman; Leandro L. Resurreccion; Maria Beatriz P. Gepte (SpringerOpen, 2019)
Abstract Background Evaluating blood ordering and subsequent development of a blood ordering schedule can decrease over-ordering of blood among pediatric surgical patients. The objective is to assess our practice of blood utilization using various blood utilization indices and calculate the Maximal Surgical Blood Order Schedule (MSBOS). This is a cross-sectional study for 3 years that included patients (≤ 18 years old) who underwent major surgical procedures in the Philippine Children's Medical Center. Data included type of surgery, age and sex, number of units crossmatched, number of units transfused, and timing of transfusion. Indices were calculated. Results This study revealed that the utilization rate was only 39.1% of blood among a total of 5314 cases done. The indices were analyzed according to different procedures among different age groups. Procedures for head and neck, colorectal, ostomy, solid tumors, genitourinary abnormalities, upper gastrointestinal, and appendectomy had CT (crossmatched to transfusion) ratio exceeding 2.0, indicating inappropriate blood ordering. Major abdominal, major thoracic, and hepatobiliary surgery all have CT ratio < 2.0. MSBOS was calculated, and a requisition of 1 unit of blood among patients undergoing these procedures is suggested. Conclusions The MSBOS is largely utilized to the adult population but its creation can also be utilized among pediatric patients. Our data shows that in majority of elective pediatric surgical procedures, routine crossmatch is not necessary which is proven by our high underutilization of requested blood products.